Group Guidance of Mind Mapping to Improve Critical Thinking Skills (Universitas Negeri Semarang, 2019)
This study attempted to examine the effectiveness group guidance of mind mapping to improve critical thingking skills. The study used pre-test and multiple post test method. The subjects in this study were eight students of grade tenth from Vocational Public High School (SMK, Sekolah Menengah Kejuruan) Negeri 2 Semarang. The data collection process utilized critical thinking scale targeting on six aspects, they are: interpretation, analysis, evaluation, conclusion, explanation, and self-regulation. The analysis used repeated measure ANOVA. The results showed the significant increase in critical thinking (F2.14 = 74.66 p < 0.01). The finding of this study confirmed that the group guidance of mind mapping is effective in improving critical thinking skills of students in SMK Negeri 2 Semarang.